Integration of transcriptome and proteome data reveals ochratoxin A biosynthesis regulated by pH in Penicillium citrinum. Issue 74 (3rd October 2017) - Zhao, Lina; Peng, Yaping; Zhang, Xiaoyun; Li, Jun; Zheng, Xiangfeng; Yang, Qiya; Apaliya, Maurice Tibiru; Zhang, Hongyin
Abstract : Proteomics and transcriptomics of P. citrinum under pH 5 (highest OTA-production) and pH 3 (not produce OTA) were analyzed to reveal the possible mechanism of OTA biosynthesis in P. citrinum. Abstract : Ochratoxin A (OTA) has been found in a wide range of commodities and is highly toxic to both humans and animals. Therefore, a good understanding of the mechanisms of OTA production by fungi will contribute to the development of eco-friendly methods to mitigate this toxin. In this study, the results showed that Penicillium citrinum X9-4, which was isolated from infected grapes in our laboratory, produced the highest amount of OTA at pH 5 in culture media, and toxin production was restrained under an acidic environment (pH 3). Then, differentially expressed proteins of P. citrinum X9-4 cultured under these two conditions were analyzed by proteomic technology. Additionally, through the analysis of the transcriptome data of P. citrinum cultured at pH 3 and 5, the differentially expressed genes have been found to be involved in many metabolic pathways including amino acid transport and metabolism, transport and metabolism of carbohydrates, inorganic ion transport and metabolism, biosynthesis of secondary metabolites, and energy and supply metabolism, which are likely to be involved in the regulation of OTA biosynthesis. It was also revealed that the expression levels of some OTA synthesis-related enzymes, such as acetyltransferase, acyl coenzyme A oxidase, alcohol oxidase, cytochrome P450, acetyl xylan esterase, and turn ketol enzyme, and genes for the regulation of toxin synthesis pathways were reduced under acidic culture conditions.